2009
DOI: 10.1038/ijo.2009.143
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin increases 172ThrAMPK phosphorylation and insulin-induced p473SerAKT while impairing adipocyte differentiation

Abstract: Objective: Lactoferrin is a pleiotropic glycoprotein of the innate immune system with known effects on immunomodulation and cell differentiation. To gain an insight into the interaction among obesity, inflammation and insulin action, we aimed to examine the effects of lactoferrin on adipogenesis and the response to insulin in human hepatocarcinoma (HepG2) and 3T3-L1 cell lines. Design: The cells were cultured with increasing lactoferrin concentration under non-inflammatory, inflammatory and standard conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 31 publications
2
51
2
Order By: Relevance
“…Yagi et al and Moreno-Navarrete et al reported similar effects of LF on the differentiation of 3T3L1 and MC3T3-G2/PA6 cell lines into adipocytes 9,11 . This phenomenon may involve low-density lipoprotein-related protein 1 LRP1 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Yagi et al and Moreno-Navarrete et al reported similar effects of LF on the differentiation of 3T3L1 and MC3T3-G2/PA6 cell lines into adipocytes 9,11 . This phenomenon may involve low-density lipoprotein-related protein 1 LRP1 .…”
Section: Discussionmentioning
confidence: 72%
“…However, these previous studies were not focused on visceral fat. Recently, two studies have demonstrated the in vitro effects of LF on preadipocytes, where LF suppressed the differentiation of adipocytes in MC3T3-G2/PA6 cell lines 9 derived from the calvaria of mice 10 , as well as the differentiation of 3T3-L1 adipocytes established from a mouse embryo 11 . We reported the effects of bLF metabolites produced in the stomach and small intestine by the digestive enzymes pepsin and trypsin in an in vitro study 12 .…”
Section: Introductionmentioning
confidence: 99%
“…More work is needed to determine whether bLf presents a doseresponse action and whether early bLf exposition allows symmetrical catch-up growth, including a proportional gain of lean, fat, and bone mass. In this sense, the activator effects of bLf on osteoblasts in rodents (20) and the presence of endogenous Lf during the early phases of the human endochondral ossification (21) suggest that Lf harbors a bone-promoting action whereas its effects on adipogenesis remain more elusive (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…All of these results suggest that bLF treatment can reduce the risk of colon carcinogenesis and have anti-tumor activity in humans. (iv) Lactoferrin is also reported to increase AMPK phosphorylation (91).…”
Section: Randomized Controlled Trialsmentioning
confidence: 96%